Elite BMX cyclists use individual strategies for a successful start - Janssen, I.; Oude Alink, A.; Frielink, F. (ISBS Proceedings Archive (Michigan), 2018)
A fast start during BMX racing is strongly related to superior performance. The purpose of this study was to identify which aspects of starting technique were related to a further distance after 1 second, an indication of an advantageous starting position. Significant between-cyclists differences were found in set position kinematics and starting technique. Whilst each cyclist had specific aspects of the start related to superior performance, two of the cyclists had strong correlations with vertical velocity of the bicycle at gate drop and at 1 second, indicating the higher the wheel was lifted, the further the distance reached after 1 second. These data provide further insight into how BMX cyclists propel the bicycle from a stationary position to attain an advantageous position as quickly as possible.